Pewarisan Ketahanan Cabai (Capsicum annuum L.) terhadap Antraknosa yang Disebabkan oleh Colletotrichum acutatum - Muhamad Syukur; Sriani Sujiprihati; Jajah Koswara; , Widodo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Anthracnose is one of the most destructive disease of pepper in Indonesia. Colletotrichum gloeosporioides and C. acutatum have been reported to be predominant species in pepper fields of Asian countries including Indonesia. Inheritance of resistance to anthracnose caused by C. acutatum was studied in Capsicum annuum populations derived from a cross between resistant line 'C-15' and susceptible line 'C-2'. Twenty green pepper fruits from each plant were inoculated with PYK 04 isolate. This experiment showed that there was no maternal effect based on t-test of F1 and F1R. Segregation of resistance and susceptibility in the F2 fitted a normal distrubution, indicated that resistance was controlled by polygenic genes. Eight effective factors were responsible for anthracnose resistance. The degree of dominance was partially recessive. Gene effects for resistance to anthracnose were additive and dominance. Additive variance was larger than dominance variance. Broad-sense heritability values were high but narrow-sense heritability values were medium. Selection for resistance to C. acutatum on pepper breeding programme should be conducted on later generation. Key words : Inheritance, anthracnose, resistance, pepper, Colletotrichum acutatum